Perancangan Expert System Development Life Cycle pada Sistem Pakar Forward Chaining Sebagai Media Pembelajaran - Putri, Diah Ika; Sidiq, Purnomo (JOEAI (Journal of Education and Instruction), 2020)
The purpose of this research is to create and develop learning media in the form of applications used for plant identification in The Division of Pinophyta. The approach used is conventional approach with Expert System Development Life Cycle (ESDLC) method from Durkin, the inference mechanism used is Forward Chaining, while the software, used for Data Base Management System (DBMS) is MySQL, Unified Modeling Language (UML), Personal Home Page (PHP). Based on the results of the application assessment test in general obtained results that this expert system application deserves to be used as a learning media with criteria for Quality of end-user interface design (55.5%), Engagement (52.3%), Interactivity (64.3 %) and Tailorability (52.4%). Conclusion, application made by Expert System Development Life Cycle (ESDLC) method, with Forward Chaining inference mechanism worthy to be used as a learning medium of plant identification in Divisio Pinophyta. Keywords: Application, Plant Identification, Learning Media, Expert System, Forward Chaining